Determination of tissue tracer transit of Technetium-99m-mercaptoacetyltriglycine diuretic renography in infants with suspected ureteropelvic junction obstruction - A multicenter prospective observational study - Luithle, Tobias; Obermayr, Florian; Dittmann, Helmut; Engel, Corinna; Etzler, Andrea; Kosch, Ferdinand; Menke, Ines Theresa; Schäfer, Mattias; Schuster, Tobias; Younsi, Nina; Fuchs, Joerg (Journal of pediatric urology, 2023)
Introduction - There is an ongoing controversy regarding management of ureteropelvic junction obstruction in infants, with a shift towards a non-operative approach. However, precise predictors of outcome are lacking. Recent studies postulated a high prognostic value of Technetium-99m-mercaptoacetyltriglycine tissue tracer transit with regard to the development of an impaired differential renal function and its potential improvement following pyeloplasty. - Objective - To evaluate the prognostic value of Technetium-99m-mercaptoacetyltriglycine tissue tracer transit for the occurrence of changes in differential renal function in infants with suspected unilateral ureteropelvic junction obstruction in a prospective observational multicenter study. - Study design - Infants below 3 months of age with a unilateral isolated hydronephrosis ≥ grade 3 received ultrasound and Technetium-99m-mercaptoacetyltriglycine diuretic renography at two different time points (timepoint 1 and timepoint 2). Data were analyzed at local centers and at the study center and were collected in an internet-based database system. Tissue tracer transit was determined for each diuretic renography, inter-observer variation for tissue tracer transit and standard parameters for judgement of differential renal function development were assessed. - Results - Thirty-seven patients were analyzed. Median age was 11 weeks (7-15) at timepoint 1 and 26 weeks (19-33) at timepoint 2. A delayed tissue tracer transit at timepoint 1 was not associated with deterioration of differential renal function at timepoint 2 in both, locally (10/37 cases) and centrally (4/37) analyzed cases. However, sensitivity and specificity were poor. The intraclass correlation coefficient comparing local and central findings of tissue tracer transit and renal drainage demonstrated poor or fair agreement. Analysis of standard parameters for differential renal function development revealed a prognostic value only for the dichotomized anteroposterior renal pelvic diameter (APD, p = 0.03, 95%-CI 1.2-22.2). - Discussion - Regarding the primary endpoint of our study, we could not confirm the hypothesis that delayed tissue tracer transit reliably predicts a subsequent decline in differential renal function in the cohort of patients studied. Whether the low age of the patients, technical problems in the correct assessment of tissue tracer transit by the investigator in early infancy, the study design, or the parameter itself played a role is debated. - Conclusion - In the presented setting tissue tracer transit was not useful as a predictive parameter for deterioration of differential renal function in infants with suspected unilateral ureteropelvic junction obstruction. Sensitivity and specificity of tissue tracer transit were not sufficient for risk stratification. Improved utility of tissue tracer transit as a marker might be achieved using a different study setting.Summary figureSummary figure